Original articleCerebellopontine angle tumours: radiologic-pathologic correlation and diagnostic difficulties - Iżycka-Świeszewska, Ewa; Szurowska, Edyta; Kloc, Wojciech; Rzepko, Robert; Dubaniewicz-Wybieralska, Mirosława; Skorek, Andrzej; Stempniewicz, Mirosław (Folia Neuropathologica, 2006)
A group of 119 cases of cerebellopontine angle (CPA) tumours was studied looking at the pathological composition, relative incidence of tumour types, their radiological features and the pathological-radiological correlations. Tumours with preoperative radiological diagnosis and verified pathologically were analyzed. Histopathologically the material consisted of 77 schwannomas and 42 non-acoustic tumours. Radiological retrospective evaluation of CT and/or MRI documentation was performed in 84 patients. The tumours were classified according to Koos’s staging scale. Diagnostic discrepancies (histopathological vs radiological) according to the clinical stage of CPA tumours were analyzed. In our series non-acoustic tumours made up 37% of CPA lesions. Sharp tumour-pyramis angle and intracanalicular fraction are not exclusive features of schwannomas. Tumours in stage IV are the most heterogeneous and diagnostically difficult group.